PENGARUH KEBIJAKAN ONE CHINA POLICY TERHADAP KEDAULATAN WILAYAH NEGARA TAIWAN DITINJAU DARI HUKUM INTERNASIONAL: The Influence of the One China Policy on Taiwan’s Territorial Sovereignty From the Perspective of International Law - Firman, Hamdi Firdaus; Wibowo, Aji (AMICUS CURIAE, 2024)
Article 1 paragraph 1 of the 1933 Montevideo Convention Concerning State Rights and Duties explains that if a country is recognized as a sovereign country it must fulfill the conditions described therein, then the problem is what causes the One China Policy to threaten the territorial sovereignty of Taiwan according to law international law and how legal settlements can be carried out by Taiwan to be able to maintain the sovereignty of its country's territory from the One China Policy. Answering these two problems can be overcome by the method used by conducting normative legal research on the sources of international law on which they are based. Data processing is done qualitatively, for drawing conclusions using a deductive mindset. Based on the analysis that has been done, it can be concluded that 1) Taiwan can be recognized as a country, but due to the lack of recognition from other countries, China is still seeking reunification with Taiwan 2) Taiwan can carry out legal settlements in order to maintain its sovereign territory 3) China's recognition of Taiwan is not justified because the country has been formed since before the recognition of the country.